(untitled) (Al-Academy, 2025)
The problem of the research tagged (commercial advertisements and their role on consumer behavior) was how to effectively influence consumer behavior. The importance of the research lies in shedding light on the study most types of commercial advertisements, or demonstrating the extent to which they can influence consumer behavior. The research aims to demonstrate the role of commercial advertisements on consumer behavior by influencing his awareness and attitudes, as well as influencing his purchasing decision. The limits of the research included all consumers of products and services of all types and uses, regardless of the consumers’ economic, cultural and social capabilities, and regardless of their mental and physical capabilities. The theoretical framework contained three researches. The first research included types of communication means and the concept of persuasive communication. As well as the topic of promotional activity and its importance, as well as a statement of the most important applications of advertising means. The second section dealt with the concept of the media and the concept of advertising, and an explanation of the functions and objectives of advertising, as well as the topic of innovative thinking and ideas in advertising, and the specifications of a successful advertising idea, in addition to addressing the topic of advertising ethics. The third section specializes in studying consumer behavior and purchasing behavior, and explaining the role of honest and false advertisements in changing the behavior of the individual consumer, while mentioning the factors influencing the behavior and purchasing decision of the individual. The most important results and conclusions reached were the following: 1. The distinguished advertisement arouses interest through the use of modern technology in its production, through which it is possible to arouse the consumer’s motives for ownership so that he can subsequently interact with the offered product to him and entice him to buy it. 2. False and misleading advertising about the nature of the industrial product, its composition, source or brand name may create an unreal or misleading impression on the consumer and encourage him to buy such a fake product. 3. Advertising activity seeks to change consumer behavior by providing all information and temptations that would change his desires and preferences for the various types of goods and services offered to him. 4. Understanding consumer behavior, motivations, and desires, and analyzing the factors affecting his consumer behavior, and how he makes the decision to buy or not, is the ultimate goal of marketing and advertising projects. Finally, recommendations and suggestions related to the research topic were presented.